If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 1) + 4 = -23 Reorder the terms: 3(1 + 3x) + 4 = -23 (1 * 3 + 3x * 3) + 4 = -23 (3 + 9x) + 4 = -23 Reorder the terms: 3 + 4 + 9x = -23 Combine like terms: 3 + 4 = 7 7 + 9x = -23 Solving 7 + 9x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = -23 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = -23 + -7 9x = -23 + -7 Combine like terms: -23 + -7 = -30 9x = -30 Divide each side by '9'. x = -3.333333333 Simplifying x = -3.333333333
| 7.4x+1y=801900000 | | P=2.6x+33.0 | | 4x+2x+3x-3= | | 9x+6+x=46 | | 9x+7=-23 | | 3-4(5-7x)=5(2x+5)-2 | | y+8=-(x-9) | | 50-7y=-14 | | 100+.30x=70+.50x | | 10(.4+.5)=4g | | 66365/6=x | | 10(.04+.05g)=4g | | (-6)-(7)-(3)= | | y+5=-(x+4) | | 72-10n=-8 | | 6x-9+5x=90 | | 6(3.5y-4.2)-2.75y=134.7 | | 2x-1=x-50 | | -x-3+3=-19 | | 4(15)+2= | | 3x+1+x-2=48cm | | 3x+12-2x=11 | | 7x-10-x=20 | | =[9X-2]/3X | | y+10=6(x+7) | | x^3-ix^2+2ix+2=0 | | 7(3x+1)=-14 | | 9x+2y+7z-5x+3z-3y= | | .425= | | 10(x)2=490 | | 5.4d-2.3d+3(d-4)=16.7 | | 21(3-x)=12 |